Effect of soil depth on productivity of sorghum (sorghum bicolor) and pigeonpea (Cajanus cajan) in sole and intercropping systems - REDDY, G SUBBA; MARUTHI, V; VANAJA, M (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted rluring 1992-95 at Hyderabad, Andhra Pradesh, 10 understand the interactive effect between soil depth, rainfall and crop growth in Alfisols under ruinfed conditions. Sole crop of sorghum [Sorghum bicolor (L.) Mocnch], pigeonpca [Cajanus cajan (L.) Millsp.] and intercropping system of sorghum + pigeonpea were grown in 3 soil depths (< 10 cm, 10-20 cm and 20 cm) in rainfed to assess the influence of effective soil depth on productivity. Besides seed yields, dry matter and N uptake and other parameters like rainfall-use efficiency, moistureadequacy index, land-equivalent ratio (LER), staple-land equivalent raio (SLER) and gross returns were also worked out. In all the systems, the seed yield (523 kg/ha) increased with the increase in the soil depth. However, over the years sorghum+pigeonpea intercropping systems gave stable yields (165 kg/ha) and gross return (Rs 2 514/ha).